Grabfood App Reuse Intention of Generation Z Customers in Semarang City: What are the factors? - Aditiya Pratama Nugroho,; Aprilian Dani Bagus Setiawan,; Arshanda Pratiwi, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The study aims to investigate the factors influencing Generation Z consumers' intention to reuse the GrabFood app in Semarang City. Utilizing a quantitative approach, the research employs the Structural Equation Modeling Partial Least Squares (SEM-PLS) method to analyze relationships between variables, including brand personality, perceived usefulness, perceived ease of use, and voucher discounts. The study sampled 210 respondents, based on Kline's recommendation, focusing on Gen Z consumers familiar with digital technology. Data was collected via questionnaires with a 7 point Likert scale, ensuring robust measurements through outer and inner model evaluations. The analysis confirms the reliability and validity of the constructs, with significant outer loading values and high composite reliability scores. The results indicate that brand personality, perceived usefulness, and voucher discounts significantly influence interest in reuse, while perceived ease of use does not have a direct significant effect. The results underscore the importance of aligning brand characteristics with consumer traits, enhancing perceived usefulness and ease of use to drive continued app usage. The study provides valuable insights for marketers aiming to foster brand loyalty among tech-savvy Gen Z consumers by leveraging effective promotional strategies and reinforcing positive user experiences.